Platelet activation in experimental murine neonatal pulmonary hypertension. Issue 5 (12th March 2020) - Davizon‐Castillo, Pavel; Allawzi, Ayed; Sorrells, Matthew; Fisher, Susan; Baltrunaite, Kristina; Neeves, Keith; Nozik‐Grayck, Eva; DiPaola, Jorge; Delaney, Cassidy
Abstract: Serotonin (5‐HT) contributes to the pathogenesis of experimental neonatal pulmonary hypertension (PH) associated with bronchopulmonary dysplasia (BPD). Platelets are the primary source of circulating 5‐HT and is released upon platelet activation. Platelet transfusions are associated with neonatal mortality and increased rates of BPD. As BPD is often complicated by PH, we tested the hypothesis that circulating platelets are activated and also increased in the lungs of neonatal mice with bleomycin‐induced PH associated with BPD. Newborn wild‐type mice received intraperitoneal bleomycin (3 units/kg) three times weekly for 3 weeks. Platelets from mice with experimental PH exhibited increased adhesion to collagen under flow (at 300 s −1 and 1, 500 s −1 ) and increased expression of the αIIbβ3 integrin and phosphatidylserine, markers of platelet activation. Platelet‐derived factors 5‐HT and platelet factor 4 were increased in plasma from mice with experimental PH. Pharmacologic blockade of the 5‐HT 2A receptor (5‐HT 2A R) prevents bleomycin‐induced PH and pulmonary vascular remodeling. Here, platelets from mice with bleomycin‐induced PH demonstrate increased 5‐HT 2A R expression providing further evidence of both platelet activation and increased 5‐HT signaling in this model. In addition, bleomycin treatment increased lung platelet accumulation. In summary, platelets are activated, granule factors are released, and are increased in numbers in the lungs of mice with experimental neonatal PH. These results suggest platelet activation and release of platelet‐derived factors may increase vascular tone, promote aberrant angiogenesis, and contribute to the development of neonatal PH. Abstract : Our study utilized a murine bleomycin model of pulmonary hypertension (PH) to study the hypothesis that platelets from mice with PH circulate in an activated state and that circulating and lung platelet‐derived factors, as well as the number of platelets in the lungs of neonatal mice with PH, is significantly increased. Through an extensive characterization of the functional status of platelets from bleomycin‐treated mice, we demonstrate that mice with bleomycin‐induced PH exhibit qualitative but not quantitative platelet changes. Circulating platelets from mice with PH exhibit hyperactivity as measured directly by adhesion and aggregation under flow and the presence of activation markers and indirectly by quantification of platelet‐specific proteins in plasma. Interestingly, we have also found that the absolute number of platelets within the lungs of mice with PH is significantly higher all together suggesting that platelets could directly be promoting PH.